The Effect of Changes in Beef Prices on Beef Supply and Demand in Indonesia - Ria Kusumaningrum; Anggita Tresliyana Suryana; Farah C. Hanoum (Enrichment : Journal of Management, 2021)
The increase in population growth in Indonesia led to an increase in demand for some products, especially food demand. Food demand that exceeds domestic production makes Indonesia an importing country. In general, the problem in this research is how to develop a cattle farming strategy to increase domestic beef production in Indonesia. This study aims to analyze the impact of beef prices on the beef supply and demand in Indonesia. This study uses secondary time series data for the period 1990-2018. The research method is qualitative and quantitative. The analytical method in this study is an econometric model with simultaneous equations and is estimated using the Two-Stage Least Squares (2SLS) method. Data were processed by SAS/EST 9.4 program. This study concludes that factors that influence beef supply in Indonesia are beef production, beef import, and beef export. Demand for beef in Indonesia is influenced by domestic beef price, chicken price, egg price, and income. Domestic beef price has no significant effect on demand for beef, where a one percent decrease in beef price will increase beef demand by 0.00011 percent, while people’s income has a significant effect at the 0.05 level. The price of domestic beef itself is influenced by several factors: the price of beef in Jakarta, the price of imported beef, and the amount of domestic beef production. An increase in beef production by one percent will reduce domestic beef prices by 22.6 percent.